(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Though there have been intense debates among academic community and policy makers in India regarding meaning and scope of development and how it is strengthening and transforming the public sphere of Indian democracy at the onslaught of globalization. But at the backdrop of these debates there are certain peculiar commonalities about methods of mapping the meanings of development and envisaging the possibility of egalitarian democracy that might be more inclusive and substantive in nature so that it might cater to the needs of subaltern citizens on the one hand and create a dynamic and dialogical public sphere to sustain the egalitarian claims of Indian democracy which are being proclaimed in philosophical, socio-political and juridical texts of Indian Constitution on the other. In this research paper, the researcher would like to talk about a critical mapping of meaning of development and substantiate the claims of egalitarian democracy through a case study of Right to Food with in different regions of India and in the process of documenting this case study. An effort is made to unpack two predominant registers of democracy that narrate the nuanced aspects of development and its consequences to marginal and subaltern citizens of India. It’s primarily inter-disciplinary in nature, therefore, it would involve analytical, descriptive and hermeneutical methods and will center on multiple narratives of different actors who have been playing active role in transforming the meaning and scope of Indian democracy.